Hot-lime-mixed hemp concretes - Pavia, Sara (Springer, 2023)
Hemp-lime composites are sustainable, low-carbon, non-loadbearing materials with outstanding thermal properties and high vapour permeability, used in new construction or thermal upgrades. The abundant pores in the hemp shiv (≥70%) are blamed for the low mechanical strength, and for a high water absorption that can result in long drying times and low early strength that delay building.AQ1 Hot-lime mixing involves using quicklime as a binder, so that the exother- mic reaction of lime slaking takes place simultaneously to mixing. This paperAQ2 investigates whether hot-lime mixing can improve the properties of hemp-lime concretes. It was hoped that the heat generated on lime slaking would reduce the water intake by the shiv, block shiv pores and promoting adhesion between the shiv and the lime matrix.AQ3 The properties of the hot-lime mixed concretes agree with former authors, with densities of 430–470 kg/m 3 and strengths of 0.32 MPa (compressive) and c.0.27 MPa (flexural) at 3 months. Their vapour diffusion resistance factor of 4.62, water sorption coefficient c.4.58 kg/m2 h1/2 , thermal conductivity 0.015– 0.021 W/mK and specific heat capacity of c.1135 J/kgK are also typical of hemp concretes. The improvement in properties due to hot-lime mixing is very small. The optimum proportions and method for hot-lime mixing are investigated. The mixing process needs to avoid water competition between the shiv and the lime slaking. Mixing the hemp with quicklime prior to slaking undermines the process lowering the slaking temperature. The best mixing method involved layering the hemp over the quicklime.
Bio-based building materials
PUBLISHED
Keywords: Strength; Water Absorption Coefficient; Water Vapour Permeability; Specific Heat Capacity; Thermal Conductivity; Hot-Lime Mixing; Hemp-Lime Materials; Quicklime